Pengembangan Kreativitas Anak Sekolah Dasar melalui Program Seni dan Kerajinan Tangan di MI Miftahul Ulum - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Nasir, M Abd; Ubaidillah, Mohammad; Rafa, Muhammad; Sultonia, Ivone; Arinanta, Arya; Fauziah, Rafika; Fatmawati, Yeni; Puspito, Agung Nugroho; Prakoso, Bhim (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This social project aims to enhance the creativity of elementary school students at MI Miftahul Ulum through a program focused on arts and crafts. The program is designed not only to stimulate students' interests and talents but also to provide opportunities for them to explore their potential and create artistic and craft works that are relevant and applicable in their daily lives. This community service activity was conducted at MI Miftahul Ulum, located at Jl. Tlogo Wetan, Antirogo, Kec. Sumbersari, Kabupaten Jember, involving 30 students from the 2nd and 3rd grades. The method employed in this activity was a conventional approach, which combined direct practice with discussion sessions to enhance students' understanding and skills. The results indicate that the students participated enthusiastically and exhibited positive expressions, which supported the optimal development of their creativity. This outcome was influenced by the positive atmosphere and conducive learning environment, allowing students to be more open in expressing their creative ideas.